Carl Ritters Sechs Karten von Europa - Engelmann, Gerhard (ERDKUNDE, 1966)
Carl Ritter’s “Sechs Karten von Europa (six maps of Europe), Schnepfenthal, 1806, is the earliest physical atlas devoted to a continent. The extant manuscript maps, Ritter's, to the plates of this atlas make it possible to trace back the preparatory work to before 1802. This map series therefore originated prior to Ritter's meeting with Heinrich Pestalozzi in Iferten as well as his meeting with Alexander von Humboldt after the return from his travels in America. The atlas consists of two mountain and altitude maps with bas-relief, and four applied maps; three of these are devoted to commodity studies and one to economic geography.